Распределение температуры и температурных полей по передней и задней поверхности спирального сверла при глубоком сверлении литейных алюминиев - Маршуба, Вячеслав Павлович (НТУ "ХПИ", 2003)
The results of investigations on the determination of temperature and temperature fields on front and back surface of standard spiral drill with elements of grinding cut in the process of deep drilling of the holes in casting aluminum on modular machines are presented. The conclusions about the ways of resolution the temperature on front and back surface in depended on quantity of front and back angles and machining deep of the holes are made.
Keywords: обработка механическая; резание; инструмент режущий; стружка